Workshop Interaktif Kriptografi dan Steganografi untuk Meningkatkan Literasi Keamanan Informasi Siswa SMK - Yasir Hasan (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2026)
The rapid advancement of digital technology has increased the importance of information security literacy, particularly among vocational high school (SMK) students who are prospective professionals in the field of information technology. However, knowledge of cryptography and steganography remains limited and has not been systematically integrated into vocational education. This community service activity aimed to improve students' understanding and practical skills in implementing basic cryptographic and steganographic techniques through an interactive workshop. The activity was conducted face-to-face using a practice-based learning approach (learning by doing), which consisted of four stages: pre-workshop, workshop implementation, post-workshop evaluation, and follow-up activities. Learning methods included lectures, demonstrations, hands-on practice, collaborative discussions, and evaluation through pre-test and post-test. The workshop involved 12 vocational high school students participating in industrial internships at Universitas Budi Darma. The evaluation results showed a significant improvement in participants' learning outcomes, with the average score increasing from 43.00 on the pre-test to 80.50 on the post-test, resulting in an average gain score of 37.50 points. In addition, all participants successfully completed practical exercises involving encryption, decryption, message embedding, and message extraction. These findings indicate that an interactive workshop based on direct practice effectively enhances students' information security literacy and fundamental technical competencies in cryptography and steganography. This program can serve as an alternative model for strengthening cybersecurity literacy in vocational education through sustainable practice-oriented training.